JWST-IPA: Chemical Inventory and Spatial Mapping of Ices in the Protostar HOPS 370—Evidence for an Opacity Hole and Thermal Processing of Ices - Himanshu Tyagi; P. Manoj; Mayank Narang; S. Thomas Megeath; Will R. M. Rocha; Nashanty Brunken; Adam E. Rubinstein; Robert Gutermuth; Neal J. Evans II; Ewine F. Van Dishoeck; Samuel Federman; Dan M. Watson; et al. (The Astrophysical Journal)
The composition of protoplanetary disks, and hence the initial conditions of planet formation, may be strongly influenced by the infall and thermal processing of material during the protostellar phase. The composition of dust and ice in protostellar envelopes, shaped by energetic processes driven by the protostar, serves as the fundamental building material for planets and complex organic molecules. As part of the JWST General Observers program, “Investigating Protostellar Accretion,” we observed an intermediate-mass protostar HOPS 370 (OMC2-FIR3) using NIRSpec integral field unit and Mid-Infrared Instrument medium-resolution spectroscopy. This study presents the gas and ice phase chemical inventory revealed with the JWST in the spectral range of ∼2.9–28 μ m and explores the spatial variation of volatile ice species in the protostellar envelope. We find evidence for the thermal processing of ice species throughout the inner envelope. We present the first high-spatial resolution (∼80 au) maps of key volatile ice species H _2 O, CO _2 , ^13 CO _2 , CO, and OCN ^− , which reveal a highly structured and inhomogeneous density distribution of the protostellar envelope, with a deficiency of ice column density that coincides with the jet/outflow shocked knots. Further, we observe high relative crystallinity of H _2 O ice around the shocked knot seen in the H _2 and OH wind/outflow, which can be explained by a lack of outer colder material in the envelope along the line of sight due to the irregular structure of the envelope. These observations show clear evidence of thermal processing of the ices in the inner envelope, close to the outflow cavity walls, heated by the luminous protostar.